Exciton Dynamics in J- And H-Aggregates of a Tricarbocyanine Near-Infrared Dye - Dimitriev, Oleg P.; Zirzlmeier, Johannes; Menon, Arjun; Slominskii, Yuri; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2021)
Intermolecular interactions in J- and H-aggregates of π-conjugated molecules provide fascinating incentives for excitonic pathways. Investigation regarding exciton dynamics in aggregates of tricarbocyanine near-infrared dyes by transient absorption spectroscopy revealed unusual intermolecular communications not only within different aggregates but also between different aggregates. To this end, aggregation was accompanied by a short-lived excitonic component, that is, on the picosecond time scale, due to additional relaxation channels and a long-lived component, that is, on the nanosecond to microsecond time scales. All of the aforementioned are in sharp contrast to what was found for the monomer. For the monomer, monoexponential exciton dynamics of about 0.5 ns was registered. Overall, the long-lived component in aggregates accounts for 1-5% of all excitons. In J-aggregates, it involves the formation of charge transfer/polaron states. In mixtures of J- and H-aggregates, contributions from the long-lived component further increased. We conclude that interactions between J- and H-aggregates open additional channels for exciton relaxation. One of them is a photoinduced charge transfer from, for example, the bright state in J-aggregates to the dark exciton states in H-aggregates, from where electrons are transferred into the continuum of states.
CRIS-Team Scopus Importer:2021-06-04